Stop-motion - Purves, Barry (Lausanne, Switzerland : AVA Publishing, 2010)
Basics Animation : Stop-motion Animation teaches the skills required to develop as a creative stop-motion animator or articulated puppet maker. It explores how all the elements of film-making - camera work, design, colour, lighting, editing, music and storytelling - come together in this unique art form. Students will learn to use and exploit the particular types of movement, characters and stories that characterise stop-motion. The book is packed with tips and suggestions to help you get the most out of your own stop-motion films, accompanied by full-colour illustrations and case studies demonstrating how film-making masters through the years have used it in feature films, short films and TV series. Basics Animation: Stop-motion Animation also examines the evolution of stop-motion, from its almost accidental beginnings to a much-loved form of storytelling in its own right - one that continues to push boundaries after 110 years, is still going strong and pushing new boundaries.
Keywords: Animation (Cinematography).